Distribution Network Configuration of Drilling Material to Reduce Transportation Cost - Yonathan, Maykel; Pujawan, I Nyoman (Institut Teknologi Sepuluh Nopember, 2020)
Drilling; the main activity in upstream oil and gas industry; is important to increase oil and gas production to supply national energy demand. PT Pertamina EP is one of oil and gas companies involved in drilling activity. As drilling schedule and number is dynamic and changing continuously, there are uncertainties in demand, excess in one warehouse and shortage in another. Consequently, double costs arise in the activity of Inter-unit Assistance related to drilling materials, with the average cost in the last 5 years reaches IDR 46,261,256,305. This research aims to design distribution network configuration of drilling materials to reduce double costs in transportation, including its cost saving estimation. The research has seven stages, i.e. (1) defining distribution network design; (2) grouping; (30 mapping warehouse locations; (4) evaluating existing warehouses; (5) selecting location of distribution center; (6) cost saving; and (7) analysis. To select distribution center location, it uses method of center of gravity. The research concludes that defining distribution strategy through distribution center is able to reduce double costs. There are 4 (four) selected of distribution center locations in Kota Baru District, Muara Enim Regency, Indramayu Regency, and Kutai Timur Regency. The research estimates that this distribution network configuration design is able to save 27.77% or IDR 26,613.231,154 in transportation cost.